2021
DOI: 10.1016/j.jcv.2021.104754
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between seasonal human coronaviruses and implications for the SARS-CoV-2 pandemic: A retrospective study in Stockholm, Sweden, 2009-2020

Abstract: Objectives The four seasonal coronaviruses 229E, NL63, OC43, and HKU1 are frequent causes of respiratory infections and show annual and seasonal variation. Increased understanding about these patterns could be informative about the epidemiology of SARS-CoV-2. Methods Results from PCR diagnostics for the seasonal coronaviruses, and other respiratory viruses, were obtained for 55,190 clinical samples analysed at the Karolinska University Hospital, Stockholm, Sweden, betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
2
20
2
3
Order By: Relevance
“…Some studies suggest that prior infections with common seasonal human coronaviruses (hCoVs) impact the severity of SARS-CoV-2 infections 16,17 . Most individuals are exposed to hCoVs early in childhood [18][19][20][21][22][23] and then re-exposed to antigenically drifted forms of these viruses throughout life [24][25][26] . Common hCoVs include the HKU1 and OC43 betacoronaviruses (β-hCoVs) and 229E and NL63 alphacoronaviruses [27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that prior infections with common seasonal human coronaviruses (hCoVs) impact the severity of SARS-CoV-2 infections 16,17 . Most individuals are exposed to hCoVs early in childhood [18][19][20][21][22][23] and then re-exposed to antigenically drifted forms of these viruses throughout life [24][25][26] . Common hCoVs include the HKU1 and OC43 betacoronaviruses (β-hCoVs) and 229E and NL63 alphacoronaviruses [27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…A modified serological enzyme-linked immunosorbent assays (ELISA) assay developed by Krammer and colleagues [9,10] was implemented to examine 9,550 individuals of age rage 16-91 years old for SARS-CoV-2 S protein IgG antibodies to quantify rates of prior infection in the GCMA. Rates of S protein seropositivity in the GCMA were examined based on race, gender, geographic subregions and time, which we also compared against rates of past infection with the 4 endemic human cold-causing coronaviruses (hCoV-229E, -NL63, -OC43, and -HKU1) [11,12]. The results suggest a rate of past SARS-CoV-2 infection in the GCMA that is more than 2X the rate of verified infection by PCR molecular detection.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HCoV-NL63 infection decreases with age [16], and so we investigated if there was any correlation between age and neutralising antibody titre. Non-parametric data were log 10 transformed and analysed with a linear regression.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, it has been reported that males are more susceptible to infection with HCoV-NL63 [16], implying that they may be more likely to be seropositive, or have higher titres of neutralising antibodies than females. In our study, 38/56 males (68%) had detectable neutralising antibodies to HCoV-NL63 compared to 33/44 females (75%).…”
Section: Discussionmentioning
confidence: 99%